Bibliometric analysis of surface electromyography trends in stroke rehabilitation research - Liao, Zhiping; Li, Jianhua; Wu, Fangchao; Xia, Yunxiang; Li, Yangzheng; Ma, Lina; Wu, Lei (Frontiers in Neurology, 2025)
Stroke, as a common clinical disease, has seen its mortality rate rising globally. Muscle dysfunction after stroke seriously affects the limb function of patients. Surface electromyography (sEMG), often referred to as the ECG of muscles, can effectively evaluate changes in muscle function in stroke patients. In this study, we searched for articles in the Web of Science database up to December 2023 and utilized the “bibliometrix” package in R software (version 4.3.3) to analyze bibliographic information. We identified 908 articles published between 1979 and 2023. Citation analysis revealed 18 articles with over 100 citations. Our bibliometric analysis included 908 articles from 1,241 institutions across 49 countries or regions, with a gradual increase in the number of articles over time. The United States led in the number of publications, followed by China, South Korea, and Japan. The Northwestern University and Shirley Ryan AbilityLab Joint Research Consortium (NU-SRAL) published the most articles with 151, accounting for 16.6% of the total. Sun Yat-sen University followed with 49 articles (5.3%), and the University of British Columbia with 35 articles (3.6%). Zhang X was the most prolific author, publishing 25 articles, while Lay B. S. was the most influential, with 120 citations. The articles were published in 371 journals, with the Journal of Electromyography and Kinesiology having the highest number, totaling 37 articles, which is about 10% of the total. The most frequent keywords were “stroke” and “rehabilitation.” Our analysis indicates a significant rise in sEMG research on stroke since 2009, suggesting that this field is a promising area for future study.